Mapping Inequity: The Campus Foodscape as Pedagogy and Practice - Fanshel, Rosalie Zdzienicka; Iles, Alastair (Frontiers in Sustainable Food Systems, 2022)
Universities and colleges are fertile foodscapes for action-based education. They are physical and socio-cultural sites where pressing food systems problems play out at micro to macro scales. Structural inequities based on race, class, gender and gender identity, sexual orientation, dis/ability, and other forms of marginalization affect both access to food and to agri-food learning opportunities. In this article, we propose that students can learn through their everyday experiences of engaging with their physical and socio-cultural environment, namely the campus food system, by conducting foodscape mapping. Since 2015, the University of California Berkeley Food Institute has supported the Foodscape Mapping Project, in which students, staff, and faculty generate food systems knowledge while developing practical interventions to advance justice, equity, diversity, and inclusion (JEDI). We investigate how campus foodscape mapping might generate substantive learning about JEDI in food systems education; the kinds of learning that take place through foodscape mapping; and the educational practices and institutional structures that can support learning through foodscape mapping. We identify at least eight forms and processes of expansive learning that emerged through mapping work, using students' own insights into what they were learning. Finally, we reflect on our learning experiences in running the project, and develop broader design elements that other campuses can apply.